Venation Pattern and Venation Density of Few Native Woody Species in Linares, Northeast of Mexico - Maiti, Ratikanta; Rodriguez, Humberto Gonzalez; Marmolejo, Jose Gudalupe; Linan Gonzalez, Mayela Isabel (International Journal of Bio-resource and Stress Management, 2023)
Venation patterns represent typical vascular skeleton in a leaf lamina offering mechanical function and transport of water, carbohydrates in plants. A study was undertaken on venation pattern and venation density of few trees and shrubs in Northeast Mexico at Forest Science School, UANL, Mexico. At first the venation pattern of 30 species has been classified according to the system of Hickey (1971). Among the 30 species studied 28 species belong to Brochidodromous: while only two species belong to Craspedodromous. In the second stage, the venation architecture and venation density of only 20 species were undertaken following the clearing technique by keeping the leaves in test tubes in solutions of H2O2: NH4OH 50 for time necessary to achieve whitening leaf rib and observed in the microscope at 5X Large variation the species showed large variations in venation architectures in orientation, size, shape depicting the characteristics of each species. The species also showed variation in density of vein. Islets in few species are bounded by thin veins but traversed by thicker vein to give mechanical strength to the leaf lamina against stress showing, adaptive characteristics Among the species studied in Eysenhardtia texana had maximum vein islet density, Ebenopis ebano, Caesalpinia mexicana, Karwinskia humboldtiana, etc. possessed medium density, while Guaiacum officinale, Amyris madrensis, Sargentia greggii, had low density.